1998
DOI: 10.1055/s-2007-978892
|View full text |Cite
|
Sign up to set email alerts
|

Local Non-Synaptic Modulation of Aldosterone Production by Catecholamines and ATP in Rat: Implications for a Direct Neuronal Fine Tuning

Abstract: In addition to hypophyseal control, steroid synthesis and secretion in the adrenal cortex is also under direct local neural modulation. We obtained morphological and neurochemical evidence that a substantial proportion of the noradrenergic nerve endings lie in close proximity to zona glomerulosa cells without making synaptic contact, thus providing evidence for a direct local modulatory role of catecholamines in steroid secretion. These noradrenergic neurones, like other noradrenergic neurones in the central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…For example, ATP and UTP increase cytosolic free calcium in human thyrocytes (Schofl et al, 1995), ATP modulates aldosterone production by adrenal cortex (Szalay et al, 1998), ATP regulates prolactin release from the anterior pituitary (Stojilkovic et al, 2000) and vasopressin and oxytocin secretion from the posterior pituitary (Sperlá gh et al, 1999); ATP stimulates insulin release from the endocrine pancreas (Coutinho-Silva et al, 2001); ATP and UTP inhibit estradiol and progesterone secretion from the ovary (Tai et al, 2001) and mediate increases in intracellular calcium in Sertoli cells from testis (Ko et al, 2003). Ovariectomy significantly increased the hydrolysis of ATP, ADP, and AMP in rat blood serum, whereas estradiol replacement therapy significantly decreased the hydrolysis of adenine nucleotides, suggesting a relationship between ecto-ATPases and the hormonal system (Pochmann et al, 2004).…”
Section: Endocrinology Diabetes and Obesitymentioning
confidence: 99%
“…For example, ATP and UTP increase cytosolic free calcium in human thyrocytes (Schofl et al, 1995), ATP modulates aldosterone production by adrenal cortex (Szalay et al, 1998), ATP regulates prolactin release from the anterior pituitary (Stojilkovic et al, 2000) and vasopressin and oxytocin secretion from the posterior pituitary (Sperlá gh et al, 1999); ATP stimulates insulin release from the endocrine pancreas (Coutinho-Silva et al, 2001); ATP and UTP inhibit estradiol and progesterone secretion from the ovary (Tai et al, 2001) and mediate increases in intracellular calcium in Sertoli cells from testis (Ko et al, 2003). Ovariectomy significantly increased the hydrolysis of ATP, ADP, and AMP in rat blood serum, whereas estradiol replacement therapy significantly decreased the hydrolysis of adenine nucleotides, suggesting a relationship between ecto-ATPases and the hormonal system (Pochmann et al, 2004).…”
Section: Endocrinology Diabetes and Obesitymentioning
confidence: 99%
“…Neural release of ATP acting on cortical cells has been considered [247], although the possibility that there is a paracrine non-synaptic modulatory role for CA and ATP in the regulation of adrenocortical steroid secretion has also been raised [520]. It has been suggested that the suprachiasmatic nucleus utilises neuronal pathways to spread its time of the day message, not only to the pineal to control melatonin secretion, but also to the adrenal cortex to influence corticosterone secretion [58].…”
Section: Adrenocortical Cellsmentioning
confidence: 99%
“…It has been suggested that the suprachiasmatic nucleus utilises neuronal pathways to spread its time of the day message, not only to the pineal to control melatonin secretion, but also to the adrenal cortex to influence corticosterone secretion [58]. The cotransmitters released by nerve varicosities influence the production of aldosterone [520]. ATP potentiates both ACTH-and angiotensin II-induced steroidogenesis in bovine adrenocortical fasciculata cells [257].…”
Section: Adrenocortical Cellsmentioning
confidence: 99%
“…The enzymes that may terminate the effect of ATP are present in the nerve endings, suggesting that ATP and its metabolites influence the production of aldosterone. Thus, catecholamines and ATP play a paracrine non-synaptic modulator role of in the regulation of adrenocortical steroid secretion (Szalay et al, 1998). Stimulation of beta-adrenoreceptors, VIP receptors or the forskolin-induced activation of cAMP formation of 2-day-old rat ovaries increases the steady state levels of the mRNAs encoding P-450aromatase and FSH receptors.…”
Section: Neuroendocrine Signalsmentioning
confidence: 99%